Subsídios para o manejo da regeneração natural de Cabralea canjerana (Vell.) Mart. em floresta secundária, RS - Zimmermann, Anna Paula Lora (2018)
Cabralea canjerana (canjerana) is one of the most important species of the Decidual Seasonal Forest of Rio Grande do Sul. Although it has been much exploited in the past by the use of its wood or to clear areas for crops, due to the abandonment of agricultural areas, it is currently common to find young populations of canjerana with high density in secondary forest fragments, mainly under the canopy, by this specie to belong to the late secondary group. On this, the objectives of this work were to test the influence of the release technique on the growth of a population in a natural regeneration stage in a secondary forest in Silveira Martins, RS, to know the reasons why some plants presented buckling of the bole after the liberation and verify the morphological plasticity of the specie in different luminosities. In an area of 1925 m² were measured the total height and the diameter at 10 cm of the soil of all the plants of the specie. The release was carried out by means of a clear cut in an area of 750 m², where all species different than canjerana were eliminated. The variables diameter at 10 cm of soil and total height were measured annually for four years. In the last evaluation, were also measured the diameter and length of the crown, height of insertion of the branches and the plants were classified according to their sociological position (emergent and dominated). The periodic increment in diameter and height was higher in liberated plants, however, the release had a greater effect when carried out in plants up to 1 meter in height. Emerging trees showed greater diameter and height increments than dominated trees. The maintenance of the competition influenced the crowns of the trees, with not liberated trees presenting shorter and narrow canopies, increasing the area of the stem without branches. The liberation caused stem buckling in some trees, but these presented a capacity of reiteration after the pruning of conduction. The canjerana has morphmetric plasticity showed leaflets exposed to the highest luminosity with xeromorphic characteristics, such as leaf area reduction, greater limbus thickness and reduction of the leaflets dimentions. The chlorophyll a, b and carotenoid patterns were similar for all light conditions, evidencing also the physiological plasticity of the species and their ability to adapt to different light conditions.